(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Dietary deficiency of calcium consequently reduces serum calcium levels and has been implicated as a cause of preeclampsia. The present study was conducted to assess association of serum calcium and serum magnesium in gestational hypertensionand pre-eclampsia.Materials & Methods: 90 patients with a singleton pregnancy in the third trimester between the age group of 18-35 yearswere dividedinto 2 groups. Each group had 45 patients. Group I were cases having blood pressure (BP) ≥140/90 mmHg and group II had normal,normotensive pregnant patients (controls). Comparison of levels of serum calcium and magnesium of both the groups was done.Results: The mean serum calcium in group I was 8.21 mg/dl and in group II was 8.92 mg/dl. The mean magnesium level in group Iwas 1.68 mg/dl in group I and 1.87 mg/dl in group II. The difference was significant (P< 0.05). Systolic blood pressure & serumcalcium shows a negative correlation. The correlation between the systolic blood pressure & serum magnesium shows a strong negativecorrelation, and is significant with a p value of 0.05. Diastolic blood pressure & serum calcium shows a negative correlationwhich isstatistically significant. The correlation between diastolic blood pressure & serum magnesium is statistically significant.Conclusion: Hypocalcaemia and hypomagnesaemia could not be possible modifiable factors in the causation of hypertension inpregnancy.